Management of Character Education Quality Improvement in Realizing the Noble Morals of Middle School Students in Boarding Schools - Kartono; Iim Wasliman; Waska Warta; Deti Rostini (IJGIE (International Journal of Graduate of Islamic Education), 2022)
The current decline in the moral quality of the nation is characterized by widespread practices of Corruption, Collusion and Nepotism (KKN), conflicts (between ethnic, religious, political, youth), increased crime, decreased work ethic, and so on. The purpose of this study is to identify and analyze planning, organizing, implementing, monitoring, supporting factors, inhibiting factors and solutions. This study uses a qualitative approach with descriptive methods and data collection techniques through interviews, observations and documentation studies. The findings of this study: (1) the planning for improving the quality of character education in realizing the noble character of students has been structured quite well and systematically, but there are obstacles, namely human resources, (2) the organization has been running even though it has not been supported by adequate job analysis, (3) its implementation has been going well but has not paid attention to the resources owned, (4) the supervision has been carried out and according to the program but has not had a significant impact on improving the quality of character education, (5) supporting factors, the commitment of leaders, professional human resources, adequate facilities and infrastructure, derivative policies and partnerships but have not fully improved the quality of character education significantly, (6) inhibiting factors, weak management, commitment to human resources, inadequate infrastructure, policies, and partnerships, (7) solutions, with rotation of leaders and effectiveness of management, training and human resource development , support adequate facilities and infrastructure, strengthen derivative policies, and a partnership